High-energy harmonic mode-locked 2 μm dissipative soliton fiber lasers. (August 2015) - Yang, Nan; Tang, Yulong; Xu, Jianqiu
Abstract High-pulse-energy harmonic mode-locking in 2 μm Tm-doped fiber lasers (TDFLs) is realized, for the first time, by using a short piece of anomalous dispersion gain fiber and the dissipative soliton mode-locking mechanism. Appropriately designing the cavity dispersion map and adjusting the cavity gain, stable harmonic mode-locking of the dissipative soliton TDFL from the 2nd to the 4th order is achieved, with the pulsing repetition rates and pulse energy being 43.4, 65.1, 86.8 MHz, and 6.27, 4.32 and 3.29 nJ, respectively. The harmonic laser pulse has a pulse width of ~30 ps and a center wavelength of ~1929 nm with a spectral bandwidth of ~3.26 nm, giving a highly chirped laser pulse. Two types of soliton molecules are also observed in this laser system.